2013
DOI: 10.1002/cctc.201300141
|View full text |Cite
|
Sign up to set email alerts
|

Efficient One‐Pot Preparation of Cu‐SSZ‐13 Materials using Cooperative OSDAs for their Catalytic Application in the SCR of NOx

Abstract: The cooperative use of the Cu‐tetraethylenepentamine complex and N,N,N‐trimethyl‐1‐adamantammonium as organic structure‐directing agents (OSDAs) enabled the rationalized “one‐pot” preparation of Cu‐containing SSZ‐13 zeolites. A detailed study of different synthetic variables permitted the control of the Si/Al and Cu/(Si+Al) ratios in the final solids. Cu‐SSZ‐13 molecular sieves synthesized in alkaline media demonstrate excellent catalytic activities and good hydrothermal stabilities for the selective catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 22 publications
2
90
0
Order By: Relevance
“…This explains why hydrothermal aging effects have been so extensively studied [39][40][41][52][53][54]. Prior studies have suggested that Cu/SSZ-13 durability enhancement can be achieved in a number of ways: (1) composition optimization, that is, choosing optimized Si/Al and Cu/Al ratios [31]; (2) zeolite particle size optimization [55]; (3) new synthesis methods development [30,[56][57][58][59]; and (4) introduction of stability enhancement additives. Among these, some appear not to be as useful as others.…”
Section: Towards Rational Design Of Cu/ssz-13mentioning
confidence: 99%
See 1 more Smart Citation
“…This explains why hydrothermal aging effects have been so extensively studied [39][40][41][52][53][54]. Prior studies have suggested that Cu/SSZ-13 durability enhancement can be achieved in a number of ways: (1) composition optimization, that is, choosing optimized Si/Al and Cu/Al ratios [31]; (2) zeolite particle size optimization [55]; (3) new synthesis methods development [30,[56][57][58][59]; and (4) introduction of stability enhancement additives. Among these, some appear not to be as useful as others.…”
Section: Towards Rational Design Of Cu/ssz-13mentioning
confidence: 99%
“…From our own experience, too large of a particle size can even be detrimental due to poor heat dissipation during structure directing agent (SDA) combustion that induces rather serious thermal degradation of the SSZ-13 substrate. Also, new Cu/SSZ-13 synthesis methods, including one-pot ones, do not necessarily lead to catalysts with better stability than catalysts prepared with more traditional solution ion-exchange methods [30,[56][57][58][59].…”
Section: Towards Rational Design Of Cu/ssz-13mentioning
confidence: 99%
“…Recently, it has been described the direct synthesis of Cu-SSZ-13 [13] and other related Cu-containing silicoaluminophosphate materials, such as Cu-SAPO-34 [12d, [14]] and Cu-7 SAPO-18, [15] using the combination of an organometallic Cu-complex (Cu-TEPA) and a cooperative organic molecule as OSDA. Following a similar "one-pot" synthesis procedure combining Cu-TEPA and N,N-dimethyl-3,5-dimethylpiperidinium as cooperative OSDAs, a crystalline Cu-containing SSZ-39 material has been achieved (see supporting information for experimental details and the PXRD pattern of Cu-SSZ-39 in Figure 1).…”
Section: +mentioning
confidence: 99%
“…Recently, several examples of one-pot synthesis methods to functionalize zeolite structures with Fe and/or Cu have been reported, e.g., [18][19][20][21]. As an example, one can use a one-pot synthesis of Cu-or Fe-zeolite, where either copper or iron occupies T-atom positions in the zeolite framework structure, followed by ion-exchange using AIE or wet impregnation (WI) of the other metal.…”
Section: Introductionmentioning
confidence: 99%